Positioning Velocity Matters in Central Paroxysmal Positional Vertigo: Implication for the Mechanism - Xia Ling; Hyo-Jung Kim; Jong-Hee Lee; Jeong-Yoon Choi; Jeong-Yoon Choi; Xu Yang; Ji-Soo Kim; Ji-Soo Kim (Frontiers in Neurology, 2020)
Objectives: To elucidate the mechanism of paroxysmal central positional nystagmus (CPN) by determining the effects of head rotation velocity on the intensity of paroxysmal downbeat nystagmus induced during straight head hanging (SHH).Methods: We recruited 21 patients with paroxysmal downbeat CPN induced during SHH at the Dizziness Center of Seoul National University Bundang Hospital from September 2018 to July 2019. Twenty-one patients had manual SHH at two different lying velocities, the fast (routine) and slow, and they also underwent SHH at different rotation velocities of 10, 20, 30, and 40 °/s using a motorized rotation chair. Induced nystagmus was recorded using video-oculography and the maximum slow phase velocity (SPV) and time constant (TC) of the induced paroxysmal nystagmus were analyzed.Results: During manual SHH, paroxysmal downbeat nystagmus was invariably induced during routine SHH (fast lying down), but absent or minimal during slow positioning. During motorized SHH, the median of maximum intensity of downbeat nystagmus increased from 7.6 °/s (0–16.9) to 14.0 °/s (0–32.5), 16.5 °/s (0–44.6), and 19.1 °/s (0–55.2) as the rotation velocity increased from 10 to 20, 30, and 40°/s (P < 0.001, P < 0.001, P = 0.004; linear mixed models). In contrast, the TCs of paroxysmal downbeat CPN remained unchanged (P = 0.558, P = 0.881, P = 0.384, linear mixed models).Conclusions: The dependence of nystagmus intensity on head rotation velocity supports a disinhibited and exaggerated inhibitory rebound of the canal signals as the mechanism of paroxysmal CPN.